Surface Integrity Study of AISI D2 Steel Using Powder Mixed RBD Palm Oil-Based Dielectric Fluid in Electrical Discharge Machining Process - NORDIN BIN SALLEH, MUHAMMAD ALIFF NAZMI; Ahmad, Said (Research Progress in Mechanical and Manufacturing Engineering, 2025)
A series of regulated electrical discharges between an electrode and a workpiece immersed in a dielectric fluid removes material from the workpiece during Electrical Discharge Machining (EDM). The dielectric fluid plays a crucial role by aiding cooling, stabilizing sparks, and removing debris, all of which influence machining performance. This study examines the surface integrity of AISI D2 steel machined using a copper electrode with biodegradable Refined, Bleached, and Deodorized (RBD) palm oil, both with and without nano aluminum oxide (Al₂O₃) powder, in comparison with conventional kerosene-based dielectric fluids. The experiments varied peak current (10A, 20A, 30A) and pulse durations (50 µs, 100 µs, 150 µs), focusing on surface roughness (Ra), recast layer thickness (RL), and microhardness (MH) as key responses. The findings reveal that adding nano-alumina powder to both kerosene and RBD palm oil significantly improves surface finish and reduces recast layer thickness, with kerosene with powder achieving the thinnest RL and lowest Ra. Although kerosene generally produces a smoother surface, RBD palm oil with powder demonstrates comparable effectiveness while providing a more sustainable alternative. Microhardness near the machined surface increased across all dielectrics due to thermal effects and rapid solidification, with powder-mixed fluids aiding in controlling heat distribution and stabilizing discharges. These results indicate that powder-mixed RBD palm oil is a practical and environmentally friendly substitute for petroleum-based fluids in EDM, maintaining machining quality while aligning with global sustainability goals